Types Of Code Switching Found On Niki Zefanya’s Speech In Najwa Shihab’s Youtube Channel - Wayan, Adi Wiguna (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2025)
In the current era of globalization, it is very easy to find the phenomenon of code switching. This phenomenon is used in various sectors. Code switching can be found in the education, technology and entertainment sectors. This study focuses on the entertainment sector and aims to determine the types of code switching, namely Tag Switching, Inter-sentential Switching and intra-sentential switching contained in one of Najwa Shihab's YouTube channels entitled Ngobrol bareng Niki: yang dirindukan dari Indonesia. This research confirmed by using observation method and descriptive qualitative method in analyzing the data. Researcher collect data in several steps. Namely, opening YouTube with the keywords Najwa Shihab next, looking for videos of Najwa Shihab with Niki Zefanya with the title Chat with Niki: yang dirindukan dari Indonesia. Watching the video repeatedly to identify, then take notes the utterances that contain code switching. The theory used in this study is the theory proposed by Poplack (1980). Total of the data in this research were 21. The most dominant type used in the video is inter-sentential switching with 10 (47,6%) data. Next is 6 (28,6%) data of intra- sentential switching, and the last, tag switching is as the lowest with only 5 (23,8%) data.